2013
DOI: 10.1016/j.cub.2013.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Tension in Rapidly Moving Cells Is Determined by Cytoskeletal Forces

Abstract: We find that the membrane tension in rapidly moving keratocytes is primarily determined by a mechanical force balance between the cell membrane and cytoskeletal forces. Our results highlight the role of membrane tension as a global mechanical regulator of cell behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
260
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(295 citation statements)
references
References 44 publications
32
260
3
Order By: Relevance
“…How the distribution of traction forces regulates the shape of the leading edge is another interesting question. The plasma membrane tension of keratocytes is not uniform throughout the cell (Lieber et al, 2013(Lieber et al, , 2015. It is thus possible that the membrane tension around the rear left and right ends, where high traction forces are exerted, is A.…”
Section: Discussionmentioning
confidence: 99%
“…How the distribution of traction forces regulates the shape of the leading edge is another interesting question. The plasma membrane tension of keratocytes is not uniform throughout the cell (Lieber et al, 2013(Lieber et al, , 2015. It is thus possible that the membrane tension around the rear left and right ends, where high traction forces are exerted, is A.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that this membrane tension is important for driving cell migration both in vitro and in vivo (46,47,65). Chemically reducing membrane tension may accelerate cell spreading and lamellipodial extension (19), whereas increasing membrane tension by hypotonic treatment may cause lamellipodial and filopodial retraction (66).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we concluded that MLCK deletion led to decreased membrane tension. (18,45,47), we speculated that the membrane skeleton was impaired after MLCK deletion. The bleb formation in suspended MLCK-deficient cells also supports this speculation because the incomplete formation of the cytoskeleton underneath the membrane causes membranous blebs (48).…”
Section: Characterization Of Mlck-deficientmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that ENTH of epsin-1 binds specifically to the receptor lipid PtdIns(4,5)P 2 (20 -22), resulting in tubulation or even vesiculation (23,24) as a result of membrane bending. Upon binding to PtdIns(4,5)P 2 an additional ␣-helix, referred to as helix-0 (amino acids [3][4][5][6][7][8][9][10][11][12][13][14][15] at the N terminus of ENTH, is formed. This newly formed helix-0 inserts into the inner monolayer of the plasma membrane resulting in an asymmetry that produces membrane curvature (25,26).…”
mentioning
confidence: 99%